Sistem Pendukung Keputusan Pemilihan Team Leader Menggunakan Metode Hybrid ROC-EDAS - Gea, Dionisia Desry Aryanti (Journal Global Technology Computer, 2024)
Team Leader must have knowledge, and its own advantages in organizing and handling every company activity to achieve the company's common goals. The problem in selecting the best team leader at PT Lion Express is still lacking in objectivity. The decision-making technique in using the ROC method as a stage of finding the weight of the supporting criteria for selecting a team leader and the EDAS method is based on the theory that each alternative consists of a number of criteria that have their own values ​​by finding the highest alternative value as the selected alternative. It is expected that both methods can overcome the problem of selecting a team leader, so a Decision Support System will be built which will be designed using Visual Basic 2008 and using Microsoft Access 2007. In the Visual Basic design, the calculation and ranking process will be produced.